Isolation and characterization of sorbitol-fermenting Shiga toxin (Verocytotoxin)-producing Escherichia coli O157:H- strains in the Czech Republic - Bielaszewska, M; Schmidt, H; Karmali, M A; Khakhria, R; Janda, J; Bláhová, K; Karch, H (Journal of clinical microbiology, 1998)
Two sorbitol-fermenting (SF) Shiga toxin-producing Escherichia coli (STEC) O157:H- strains were isolated from patients with hemolytic-uremic syndrome in the Czech Republic in 1995. Their phenotypic and genotypic characteristics and genomic DNA fingerprints were identical or closely related to those of SF STEC O157:H- strains isolated in Germany in 1988 to 1997. This indicates that the Czech isolates belong to the SF STEC O157 clone which is widespread in Germany. It is the first finding of the clone outside Germany.
Keywords: hemolyticko-uremický syndrom; infekce vyvolané Escherichia coli; Escherichia coli Infections; technika náhodné amplifikace polymorfní DNA; DNA bakterií; Infant; feces; Humans; Phylogeny; kojenec; DNA fingerprinting; Random Amplified Polymorphic DNA Technique; DNA Fingerprinting; Phenotype; Sorbitol; Genotype; lidé; Hemolytic-Uremic Syndrome; Feces; Escherichia coli O157; DNA, Bacterial; shiga toxin 1; fylogeneze; Bacterial Toxins; fenotyp; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; genotyp; sorbitol; bakteriální toxiny; Česká republika; Shiga Toxin 1